2018
DOI: 10.1021/acs.joc.8b00617
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Reductive Deuteration of Tertiary Amides Mediated by Sodium Dispersions with Distinct Proton Donor-Dependent Chemoselectivity

Abstract: A practical and scalable single electron transfer reduction mediated by sodium dispersions has been developed for the reduction and reductive deuteration of tertiary amides. The chemoselectivity of this method highly depends on the nature of the proton donor. The challenging reduction via C-N bond cleavage has been achieved using Na/EtOH, affording alcohol products, while the use of Na/NaOH/HO leads to the formation of amines via selective C-O scission. Sodium dispersions with high specific surface areas are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…4 Traditionally, amide reduction reactions have been carried out using (over)stoichiometric amounts of classical reagents such as lithium aluminum hydride (LiAlH 4 ) or boranes (B 2 H 6 ), which require tedious workup procedures and generate large amounts of waste. 5 Recently emerged non-catalytic protocols using samarium iodide (SmI 2 )/amine/H 2 O, 6 sodium dispersions with different proton donors, 7 or sodium hydride (NaH) with zinc halides (ZnX 2 ; X = Cl, I) 8 have similar limitations. Different catalytic strategies have been developed for the reduction of amides to amines under hydrosilylation, 9 hydroboration 10 and transfer-hydrogenation 11 conditions, which are methodologies with wide applicability for functionalized amides, but they suffer from low atom-efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…4 Traditionally, amide reduction reactions have been carried out using (over)stoichiometric amounts of classical reagents such as lithium aluminum hydride (LiAlH 4 ) or boranes (B 2 H 6 ), which require tedious workup procedures and generate large amounts of waste. 5 Recently emerged non-catalytic protocols using samarium iodide (SmI 2 )/amine/H 2 O, 6 sodium dispersions with different proton donors, 7 or sodium hydride (NaH) with zinc halides (ZnX 2 ; X = Cl, I) 8 have similar limitations. Different catalytic strategies have been developed for the reduction of amides to amines under hydrosilylation, 9 hydroboration 10 and transfer-hydrogenation 11 conditions, which are methodologies with wide applicability for functionalized amides, but they suffer from low atom-efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…When phenothiazine reacted with acrylonitrile and N , N ‐dimethyl acrylamide under base catalysis, the corresponding aza‐Michael adducts 9 and 11 were obtained in good yields. Notably, compounds 9 and 11 can be formally transformed directly to commercial drug molecule promazine ( 12 ), used for the treatment of schizophrenia (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study began with the optimization of the reaction conditions for the C-N σ bond cleavage process in azetidinyl amides, using 1a as a model substrate. In the previous work, we have demonstrated that 1a can be converted into the corresponding alcohol via C-N cleavage, using Na/EtOH [5]. We hypothesized that the absence of the proton donor would suppress the amide reduction pathway, and lead to the formation of 2a via the C-N σ bond cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Amide is among the most ubiquitous functional groups [1]. Although the reductive functionalization of amides has been studied extensively, the majority of strategies have focused on the amide reductions via C-O or C-N cleavage, to afford the corresponding amines or alcohols (Scheme 1) [2,3,4,5,6,7,8,9,10,11]. Only a few examples were reported for the amide bond functionalization via the selective activation of the non-carbonyl, C-N σ bond, despite its considerable potential in the synthesis of amide linkage in both chemistry and biology (Scheme 1) [12,13].…”
Section: Introductionmentioning
confidence: 99%